2016
DOI: 10.1007/s40753-016-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Mathematicians’ Conceptual and Ideational Mathematics about Continuity of Complex-Valued Functions

Abstract: Adopting Schiralli and Sinclair's notions of conceptual mathematics (CM) and ideational mathematics (IM), we investigated mathematicians' reasoning about continuity of complex-valued functions. While CM centers on formal mathematics as a discipline, IM focuses on how an individual perceives formal mathematics. There were four IM notions that the mathematicians used to convey the idea of continuity for complex-valued functions: control, topological features, preservation of closeness, and paths. The mathematici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Additionally, in the discipline there are studies such as those by Hanke (2020) and Soto-Johnson et al (2016) that aim to understand how professional mathematicians perceive and communicate different mathematical tools and concepts of CA to their peers. This kind of research has revealed that attributing geometric meanings to purely algebraic expressions is not a trivial task.…”
Section: Discussion: the Use Of Geometric Formulations In Mathematics...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the discipline there are studies such as those by Hanke (2020) and Soto-Johnson et al (2016) that aim to understand how professional mathematicians perceive and communicate different mathematical tools and concepts of CA to their peers. This kind of research has revealed that attributing geometric meanings to purely algebraic expressions is not a trivial task.…”
Section: Discussion: the Use Of Geometric Formulations In Mathematics...mentioning
confidence: 99%
“…Studies in Mathematics Education have been carried out to address this type of problems. For example, some research has incorporated digital technologies to attend to different mathematical objects inscribed in the theory of complex functions (D'Azevedo & Dos Santos, 2021;Dittman et al, 2016;Ponce, 2019), while some other studies investigate how undergraduate mathematics students and professional mathematicians work geometrically with them (Hanke, 2020;Oehrtman et al, 2019;Soto & Oehrtman, 2022;Soto-Johnson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using examples (Durand-Guerrier, 2016;Lockwood et al, 2016), using graphical images (Zhen et al, 2016), using analogy (Dawkins & Roh, 2016), and using metaphor (Durand-Guerrier, 2016), researchers have tried to materialize mathematical abstraction. Some researchers have tried conceptual and ideational reasoning (Soto-Johnson, Hancock, & Oehrtman, 2016), metalinguistic and mathematical reasoning (Dawkins & Roh, 2016), procedural and conceptual reasoning (Bagley & Rabin, 2016), syntactic and semantic reasoning, cognitive and metacognition reasoning (Mejía-Ramos, Weber, & Fuller, 2015) to materialize proof oriented mathematics meaningfully.…”
Section: Introductionmentioning
confidence: 99%
“…Previous empirical studies explore secondary students' [1], undergraduate students' [2][3][4][5], prospective and inservice secondary teachers' [6][7][8], and experts' [9] algebraic and geometric understanding of complex numbers in mathematics and engineering contexts. Some of these studies cover calculational aspects of complex number fluency we discuss including complex algebra [2] and changing between [8], and appropriately selecting [4], forms of complex numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies cover calculational aspects of complex number fluency we discuss including complex algebra [2] and changing between [8], and appropriately selecting [4], forms of complex numbers. While one study included a physics expert [9], we were unable to identify studies which focus on undergraduate physics students' understanding of complex numbers.…”
Section: Introductionmentioning
confidence: 99%